Motivación profesional docente y rendimiento académico en los estudiantes del 4to grado “A”de primaria en la I.E N°00537 Matilde del Águila - Alarcón Peralta, Ana Lizeth (2010)
In the Educational lnstitution N o. 00537 " Matilde Del Águila Velazques " - Rioja, in agreement to the Minutes of Evaluation during the year 2007, observes an average of academic performance between low and regularly (08-12), sorne deficiencias being demonstrated in the process education - leaming, due to the inadequate professional educational motivation, to influence positively the academic performance. The aim of the investigation was to determine the influence of the professional educational motivation in the academic performance of the students of the fourth degree of primary education in the city of Rioja in the year 2008. The logical consistency of the relation between the Professional Educational Motivation and the Academic Performance is sustained on the basis of the cognitive perspectiva, the interna! motivation of the achievement of the students and to the model of academic performance; hipotetizando that the Professional Educational Motivation will influence positively in the academic performance in the students of the fourth degree "A" of primary Education, in the Educational lnstitution N ° 00537 " Matilde Del Águila Velazques " - Rioja. The investigation is basic, of the descriptiva explanatory level, with a sample of 30 students (15 males and 15 women), to whom 1 administer a Test, and 1 gather of the averages obtained to level of the academic performance, which information has been processed, analyzed and interpretad by means of the percentage calculation, the arithmetic mean, and the coefficient of correlation. The brave results allow to establish that there does not exista significant relation of the professional educational motivation with the academic performance of the students of the Fourth Degree To of Primary Education of the I.E. N o 00537 " Matilde of the Eagle Velazques ".